2013
DOI: 10.1155/2013/847071
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Zirconium(IV) Complexes with Amino Acid Schiff Bases: Spectral, Molecular Modeling, and Fluorescence Studies

Abstract: New zirconium(IV) complexes were synthesized with bidentate ligands and characterized by elemental analysis, molar conductance measurements, molecular weight determinations, IR, electronic, NMR (1H and 13C), fluorescence and molecular modeling studies. All the complexes are 1 : 2 electrolytes in nature and may be formulated as [Zr(L)2Cl2] (where L is Schiff bases of amino acids and substituted isatin). The analytical data showed that the Schiff-base ligand acts as bidentate toward zirconium ion via the azometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For the Zr(IV) complex, it shows bands at 36,232, 26,385, 25,000, and 24,331 cm –1 , attributed to π–π*, ( n –π*, N=N), ( n –π*, C=N), and LMCT transitions, respectively, with diamagnetic properties, suggesting a distorted trigonal bipyramidal geometry around Zr(IV). 49 51 Comparative UV–vis spectra of the free Schiff base ligands (OV-Azo) and its metal complexes Ni(II), Co(II), Zn(II), Cu(II), Mn(II), and Zr(IV) in DMSO are shown in Figure 2 , showing a match between the free Schiff base and different complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Zr(IV) complex, it shows bands at 36,232, 26,385, 25,000, and 24,331 cm –1 , attributed to π–π*, ( n –π*, N=N), ( n –π*, C=N), and LMCT transitions, respectively, with diamagnetic properties, suggesting a distorted trigonal bipyramidal geometry around Zr(IV). 49 51 Comparative UV–vis spectra of the free Schiff base ligands (OV-Azo) and its metal complexes Ni(II), Co(II), Zn(II), Cu(II), Mn(II), and Zr(IV) in DMSO are shown in Figure 2 , showing a match between the free Schiff base and different complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the tetrahedral geometry has been suggested for the Cu­(II) complex. , The electronic spectra of the Zn­(II) complex exhibited bands at 36,900, 28,090, 26,525, and 16,978 cm –1 , assigned to π–π*, ( n –π*, NN), ( n –π*, CN), and d-d transitions, respectively, with diamagnetic properties, suggesting an octahedral geometry around the Zn­(II) ion. For the Zr­(IV) complex, it shows bands at 36,232, 26,385, 25,000, and 24,331 cm –1 , attributed to π–π*, ( n –π*, NN), ( n –π*, CN), and LMCT transitions, respectively, with diamagnetic properties, suggesting a distorted trigonal bipyramidal geometry around Zr­(IV). Comparative UV–vis spectra of the free Schiff base ligands (OV-Azo) and its metal complexes Ni­(II), Co­(II), Zn­(II), Cu­(II), Mn­(II), and Zr­(IV) in DMSO are shown in Figure , showing a match between the free Schiff base and different complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The suggested formula of ligands (TAMP and TIMP) and metal compounds (3)(4)(5)(6)(7)(8) were consistent with elemental analysis and 1 H NMR results. MS measurements of TAMP and TAMP-metal compounds showed that compounds were dimeric by an oxo bridge in contrast to ZrCl2-amino acid Schiff base compounds [19]. FTIR spectrum of free 2-((p-tolylamino)methyl)phenol exhibited bands at ~3416 and 3261 cm -1 corresponding to stretching vibrations of the OH and NH groups, respectively [6,14].…”
Section: Ppo and Pcl Prepared With (Tamp)3ti2(o I Pr)o2 (9)mentioning
confidence: 98%
“…The octahedral Zr(IV) complex was diamagnetic and showed bands at 270 and 373nm are due to the → * transitions within the aromatic ring and another band at 476nm is due to the → * transitions within the >C=N-chromophore in Uv-visible spectrum [22].…”
Section: Magnetic Moment and Electronicmentioning
confidence: 99%